2020
DOI: 10.1007/s00268-020-05420-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Pheochromocytoma: A Single‐Center Review of 60 Cases from South Africa

Abstract: Background There is a paucity of data on the presentation and surgical management of pheochromocytoma in developing nations, particularly in Africa. Methods This study was a retrospective review, which included all patients managed by the Groote Schuur Hospital/ University of Cape Town Endocrine Surgery unit for pheochromocytoma and abdominal paragangliomas, from January 2002 to June 2019. Results Sixty patients were included in the study, of which 33% were male and 67% female. The mean age was 47 years (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The study has a number of limitations. As a small single-center cohort, we cannot determine the overall structure of the genetic risk profile for endocrine neoplasias, including PPGL in South Africa as a whole, similar to previous genetic studies on this topic in South Africa ( 10 , 11 , 12 , 22 ). Hence, it remains to be proven in larger series whether the SDHB exon 3 deletion mutation plays a major role in PPGL risk nationally in South Africa.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The study has a number of limitations. As a small single-center cohort, we cannot determine the overall structure of the genetic risk profile for endocrine neoplasias, including PPGL in South Africa as a whole, similar to previous genetic studies on this topic in South Africa ( 10 , 11 , 12 , 22 ). Hence, it remains to be proven in larger series whether the SDHB exon 3 deletion mutation plays a major role in PPGL risk nationally in South Africa.…”
Section: Discussionmentioning
confidence: 87%
“…Identification of this founder effect in South Africa is clinically relevant, as the patients and families affected in this study had an aggressive phenotype. Further study of previously identified patients with PPGL in South Africa could provide more information on the relative frequency of the exon 3 deletion SDHB founder mutation ( 10 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the clinical characteristics and causative variants of PGLs in patients of non-European ancestry, especially those of African descent, are overall limited. Interestingly, the few studies that have examined PGL in patients from the African continent have described unique characteristics including a female predominance and a tendency for unusual ectopic locations [34][35][36][37]. One study of 54 self-identified Black patients with PCC/PGL in South Africa showed 39% had extraadrenal tumors [38], and only five patients had familial syndromes; it is unclear whether these patients were assessed for all known variants [39].…”
Section: Discussionmentioning
confidence: 99%
“…The largest published series to date includes 60 patients, of whom 33% were male and 67% were female, with a mean age of 47 years (range 14-81). 41 No data on ethnicity were recorded for these cases. A series of 54 black patients with phaeochromocytoma from a hospital in Gauteng showed a female to male ratio of 3.2:1 and an age range from 8 to 57 years.…”
Section: Discussionmentioning
confidence: 99%